EXPLORATION OF INTERNALISED STIGMA AND EMOTIONAL DISTRESS AMONG INDIVIDUALS WITH PSYCHIATRIC ILLNESSES - Sheikh, Sibgha; Bilal Baig, Khawer; Ashraf, Nayab (Journal of Pakistan Psychiatric Society, 2025)
OBJECTIVES To explore the level of internalized stigma and emotional distress in people with different psychiatric disorders including anxiety disorders, mood disorders, and obsessive compulsive disorders. STUDY DESIGN Cross-sectional comparative study PLACE AND DURATION OF STUDY Department of Psychiatry at the Services Hospital, Lahore, Pakistan from 1st June 2021 to August 2022 (period of one year). METHOD A total of 180 participants which comprised 60 with each psychiatric condition (anxiety disorders, mood disorders, and obsessive compulsive disorders) were recruited from psychiatric department (Ward/OPD) using Purposive and convenience quota sampling technique. Internalized stigma was measured using the Internalized Stigma of Mental Illness Inventory (ISMI) Scale, while emotional distress was examined using the Perceived Emotional Distress Inventory (PEDI). RESULTS Variations of stigma in different psychiatric populations experiencing mood disorders, anxiety disorders and OCD were observed. It was found that the higher the experience of internalized stigma, higher the levels of emotional distress. CONCLUSION The research observed the variations in impact of internalized stigma among individuals with mood disorders, anxiety disorders, and OCD. It was also found that the higher the experience of internalised stigma, the higher were the levels of emotional distress.